Relavansi Pemikiran Pendidikan Cokroaminoto Dengan Anis Baswedan - Edi sumanto (At-Ta'lim : Media Informasi Pendidikan Islam, 2016)
Abstract : The journal wants to find the relevance of educational thought Clark Aminotowith Anis Baswedan because it includes people who care about education. Nationaleducation desired by H.O.S. Tjokroaminoto is patriotism that is desperately conducteducation to instill a feeling of nationality; have the courage always to instill a sense ofcourage, especially jihad